FINANCIAL DISTRESS DAN TAX AVOIDANCE: POTRET PERUSAHAAN MANUFAKTUR DALAM ANALISIS DESKRIPTIF KUANTITATIF - Sam, Benedikta Fristhalie; Umyana, Ayu; Hamzani, Umiaty (LPPM Universitas Bina Bangsa, 2024)
Tax avoidance can be driven by several factors, including declining financial conditions. Based on some cases that have occurred in companies in Indonesia, the research questions for this study are: 1) Do companies experiencing financial difficulties tend to engage in tax avoidance? 2) Do companies not experiencing financial difficulties also tend to engage in tax avoidance? The purpose of this study is to investigate and describe the tendency of tax avoidance based on the financial conditions of companies. The sample for this study includes manufacturing companies in the sub-sectors of Household Goods, Leisure Goods, and Tobacco listed on the Indonesia Stock Exchange for the period 2020-2022. The sample selection was done using purposive sampling, resulting in 33 samples from 11 companies that met specific criteria. This research is a descriptive quantitative study, describing financial distress using the Springate S-Score method and tax avoidance using the Cash Effective Tax Rate. The scores and ratios were then analyzed using Microsoft Excel Office 2021. The results of this study indicate that companies experiencing financial difficulties tend to engage in tax avoidance practices. There are also companies that are not experiencing financial difficulties but are still indicated to be engaging in tax avoidance practices. Additionally, it was found that some companies categorized as experiencing financial difficulties do not engage in tax avoidance practices